PENGARUH MINAT BELAJAR TERHADAP HASIL BELAJAR TINGKAT SMA/SMK - Muhammad Ali Wafa; Didit Darmawan (Jurnal Tawadhu, 2025)
This study aims to examine the effect of learning interest on student learning outcomes at the SMA/SMK level through a descriptive qualitative approach with a literature study method. Based on the review of various sources and previous research findings, it is concluded that interest in learning is an important factor that significantly affects students' academic achievement. Learning interest characterized by enthusiasm, focus, and active involvement is proven to contribute to improving learning outcomes, both directly and through mediating variables such as motivation, independence, and learning discipline. External factors such as parenting style, the role of teachers and a conducive learning environment also play an important role in shaping students' interest in learning. In the context of digital technology development, utilizing technology-based learning media is an effective strategy to increase students' interest and participation in learning. Therefore, collaboration between schools, teachers, parents, and the appropriate use of learning technology is key in fostering students' interest in learning, so that it has a direct impact on optimizing learning outcomes.